Effect of the infill panels in the floor response spectra of an 8-storey RC building - André Furtado (2021)
One of the significant challenges concerning earthquake risk mitigation is the seismic vulnerability assessment of existing buildings that were not designed according to modern codes. Several authors recognized that the infill walls might significantly affect the seismic response of reinforced concrete structures (RC). Still, they are treated as "non-structural" elements by the national and international codes and they are not considered in the seismic assessment of existing RC buildings, and their impact on the seismic response of the structure is neglected. This manuscript aims to study the seismic response of an 8-storey RC structure simulated in the software OpenSees with and without masonry infill walls. The masonry infill walls were simulated considering their in-plane and out-of-plane (OOP) behaviour interaction. Two different studies were performed. First, the study of the impact of the infill walls in the global building seismic response and after that the study of the infill walls seismic performance. Several incremental dynamic analyses were carried out for these studies to study floor accelerations and velocities and determine peak floor acceleration and peak floor velocity. At the same time, floor response spectra were drawn for the design peak ground acceleration, according to Eurocode 8. Acceleration-Displacement Response Spectrum is also obtained and presented according to Eurocode 8. The OOP accelerations and OOP velocities of the masonry infill walls were recorded for all the input ground-motions. The maximum OOP accelerations and velocities reached by the infill panels at each floor were obtained and discussed. The respective infill acceleration and infill acceleration-displacement response spectrum and infill velocity response spectra were then derived and presented. Finally, the amplification of the infills OOP accelerations along the building height will be evaluated and compared with the Eurocode 8 demands. The results show that the infills increase the peak floor accelerations and modify the floor response spectra. The infills OOP accelerations are always 1.2-2 times higher than PFA. The infills acceleration response spectra do not change with the increase of the building height.